Foreign Direct Investment and Infrastructure Development in Indonesia: Evidence from Province Level Data - Fitriandi, Primandita; Kakinaka , Makoto; Kotani, Koji (Asian Journal of Empirical Research, 2014)
Attracting foreign direct investment (FDI) has been an important policy agenda under institutional and regulatory reforms toward the decentralized system in Indonesia. Infrastructure development has been acknowledged as a crucial condition to attract foreign direct investment. This study empirically examines the relationship between infrastructure development and FDI inflows at the province level in Indonesia by using panel data of 30 provinces over the sample period of 2000-2009. As a proxy to infrastructure development, this study uses four measures of hard infrastructure: electricity, road length, water capacity, and water distribution. Our empirical analysis shows that infrastructure development would promote FDI inflows. In addition, the result presents that provinces with small-sized government, which is measured by government expenditure, attract more FDI inflows. These results are also confirmed by the count data analysis of FDI projects. The need of better infrastructure with small-sized government suggests that the policy authority should utilize private investment through various schemes, such as public private partnership (PPP).